Residency training programs to support residents working in First Nations, Inuit, and Métis communities - Marghalara Rashid; Julie Nguyen; Wayne Clark; Jessica L. Foulds; Ida John; Ming-Ka Chan; Molly Whalen-Browne; Pamela Roach; Melanie Morris; Sarah Forgie (BMC Medical Education, 2025)
Abstract Background To gain culturally appropriate awareness of First Nations, Inuit and/or Métis Health, research suggests that programs focus on sending more trainees to First Nations, Inuit and/or Métis communities Working within this context provides experiences and knowledge that build upon classroom education and support trainees’ acquisition of skills to engage in culturally safe healthcare provision. This study examines residents' and faculty members' perceptions of how residency training programs can optimize First Nations, Inuit and/or Métis health training and support residents in gaining the knowledge, skills, and experiences for working in and with First Nations, Inuit and/or Métis communities. Methods A qualitative approach was used, guided by a relational lens for collecting data and a constructivist grounded theory for data interpretation. Theoretical sampling was used to recruit 35 participants from three main study sites across two western Canadian provinces. Recruitment, data collection, and analysis using constructivist grounded theory occurred concurrently to ensure appropriate depth of exploration. Results Our data analysis revealed five themes: Five themes were generated: Complexity of voluntourism as a concept; Diversity of knowledge representation required for developing curriculum; Effective models of care for First Nations, Inuit and/or Métis health; Essential traits that residents should have for working in First Nations, Inuit and/or Métis communities; and Building relationships and trust by engaging the community. Conclusions First Nations, Inuit and/or Métis Health should be prioritized within Canadian postgraduate medical education. Equipping trainees to provide holistic care, immersing in and learning from First Nations, Inuit and/or Métis communities is essential for developing the next generation of clinicians and preceptors. We present educational recommendations for residency programs to optimize First Nations, Inuit and/or Métis health educational experiences and provide ...